1993
DOI: 10.1159/000177781
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dietary Casein and Soybean Protein Effects on Plasma Lipid and Gastrin Levels, Hepatic &Delta;<sup>6-</sup>Desaturase Activity and Coronary Arteriosclerosis in Male Sprague-Dawley Rats

Abstract: An increased concentration of gastrin was observed in plasma of male Sprague-Dawley strain rats fed on soybean protein diet for a 9-month period, compared with rats fed on casein diet. Both diets contained 0.5% (w/w) cholesterol. Protein-dependent differences were also observed in the fatty acid pattern of hepatic phospholipids, hepatic Δ6-desaturase activity, and plasma cholesterol. No signs of arteriosclerosis were observed in the aortas. Sixty percent of the hearts showed various degrees of lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Lindhom et al (1993) found the same results in rats who were fed a diet containing 20 per cent casein or soy protein supplemented with 0.5 per cent of cholesterol for 28 days. Moreover, in rats who were fed with a diet containing 20 per cent casein or soy protein and supplemented with 10 per cent of the olive oil and supplemented with cholesterol for 28 days, Eklund and Sjoblom (1986) noted that when dietary cholesterol increases from 0 to 0.25 per cent, the content of serum TG increases with casein or soy protein combined.…”
supporting
confidence: 52%
“…Lindhom et al (1993) found the same results in rats who were fed a diet containing 20 per cent casein or soy protein supplemented with 0.5 per cent of cholesterol for 28 days. Moreover, in rats who were fed with a diet containing 20 per cent casein or soy protein and supplemented with 10 per cent of the olive oil and supplemented with cholesterol for 28 days, Eklund and Sjoblom (1986) noted that when dietary cholesterol increases from 0 to 0.25 per cent, the content of serum TG increases with casein or soy protein combined.…”
supporting
confidence: 52%
“…For experiments, both monocytes and macrophages were incubated for 24 h in serum-free media with lipoprotein additions as indicated under "Results." Lipoproteins were prepared by differential ultracentrifugation of fresh plasma from healthy donors (29).…”
Section: Methodsmentioning
confidence: 99%
“…Lipoproteins were prepared by differential ultra centrifugation of fresh plasma from healthy donors [ 16 ]. Lipoproteins were stored at -80°C with 10% sucrose and 4.8 mM EDTA, pH = 7.4, a procedure which does not affect lipoprotein integrity [ 17 ].…”
Section: Methodsmentioning
confidence: 99%